Analisis Yuridis Penerapan Diversi dan Keadilan Restoratif dalam Sistem Peradilan Pidana Anak pada Tingkat Penyidikan Demi Mewujudkan Perlindungan Anak - Gita Damaiyanti; Ramon Nofrial; Erniyanti Erniyanti (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: This study is to find out the legal arrangements for diversion and restorative justice in the juvenile justice system at the investigative level in order to realize child protection in the Riau Islands Regional Police, to find out the implementation of diversion and restorative justice in the juvenile justice system at the investigative level in order to realize child protection in the Riau Islands Regional Police and to Know the Constraints / Barriers and Solutions to diversion and restorative justice in the juvenile justice system at the investigative level in order to realize child protection in the Riau Islands Regional Police. Method: This research is normative legal research, supported by sociological/empirical research, using secondary data sources from library research to obtain a theoretical basis in the form of opinions or writings of experts, as well as to obtain information both in the form of formal provisions and data through official texts. Result: The formal criminal justice system which ultimately places children in prison status certainly brings considerable consequences in terms of child growth and development. The punishment process given to children in prisons does not succeed in making children deterrent and become better individuals to support their growth and development process, prisons often make children more skilled in committing crimes.